Structure mediation in substrate binding and post-translational processing of penicillin acylases: Information from mutant structures of Kluyvera citrophila penicillin G acylase - Chand, Deepak; Varshney, NishantKumar; Ramasamy, Sureshkumar; Panigrahi, Priyabrata; Brannigan, James A.; Wilkinson, Anthony J.; Suresh, C. G. (Protein Science, 2015)
Penicillin acylases are industrially important enzymes for the production of 6-APA, which is used extensively in the synthesis of secondary antibiotics. The enzyme translates into an inactive single chain precursor that subsequently gets processed by the removal of a spacer peptide connecting the chains of the mature active heterodimer. We have cloned the penicillin G acylase from Kluyvera citrophila (KcPGA) and prepared two mutants by site-directed mutagenesis. Replacement of N-terminal serine of the beta-subunit with cysteine (Ser beta 1Cys) resulted in a fully processed but inactive enzyme. The second mutant in which this serine is replaced by glycine (Ser beta 1Gly) remained in the unprocessed and inactive form. The crystals of both mutants belonged to space group P1 with four molecules in the asymmetric unit. The three-dimensional structures of these mutants were refined at resolutions 2.8 and 2.5 angstrom, respectively. Comparison of these structures with similar structures of Escherichia coli PGA (EcPGA) revealed various conformational changes that lead to autocatalytic processing and consequent removal of the spacer peptide. The large displacements of residues such as Arg168 and Arg477 toward the N-terminal cleavage site of the spacer peptide or the conformational changes of Arg145 and Phe146 near the active site in these structures suggested probable steps in the processing dynamics. A comparison between the structures of the processed Serb1Cys mutant and that of the processed form of EcPGA showed conformational differences in residues Arg alpha 145, Phe alpha 146, and Phe beta 24 at the substrate binding pocket. Three conformational transitions of Arg alpha 145 and Phe alpha 146 residues were seen when processed and unprocessed forms of KcPGA were compared with the substrate bound structure of EcPGA. Structure mediation in activity difference between KcPGA and EcPGA toward acyl homoserine lactone (AHL) is elucidated.
Keywords: acyl homoserine lactone; autocatalytic processing; conformational changes; KcPGA_Ser beta 1Cys; KcPGA_Ser beta 1Gly; Ntn hydrolase

Structure and function of a highly active Bile Salt Hydrolase (BSH) from Enterococcus faecalis and post-translational processing of BSH enzymes - Chand, D. (Biochim Biophys Acta., 2018)
Bile Salt Hydrolase (BSH), a member of Cholylglycine hydrolase family, catalyzes the de-conjugation of bile acids and is evolutionarily related to penicillin V acylase (PVA) that hydrolyses a different substrate such as penicillin V. We report the three-dimensional structure of a BSH enzyme from the Gram-positive bacteria Enterococcus faecalis (EfBSH) which has manifold higher hydrolase activity compared to other known BSHs and displays unique allosteric catalytic property. The structural analysis revealed reduced secondary structure content compared to other known BSH structures, particularly devoid of an anti-parallel β-sheet in the assembly loop and part of a β-strand is converted to increase the length of a substrate binding loop 2. The analysis of the substrate binding pocket showed reduced volume owing to altered loop conformations and increased hydrophobicity contributed by a higher ratio of hydrophobic to hydrophilic groups present. The aromatic residues F18, Y20 and F65 participate in substrate binding. Thus, their mutation affects enzyme activity. Docking and Molecular Dynamics simulation studies showed effective polar complementarity present for the three hydroxyl (-OH) groups of GCA substrate in the binding site contributing to higher substrate specificity and efficient catalysis. These are unique features characteristics of this BSH enzyme and thought to contribute to its higher activity and specificity towards bile salts as well as allosteric effects. Further, mechanism of autocatalytic processing of Cholylglycine Hydrolases by the excision of an N-terminal Pre-peptide was examined by inserting different N-terminal pre-peptides in EfBSH sequence. The results suggest that two serine residues next to nucleophile cysteine are essential for autocalytic processing to remove precursor peptide. Since pre-peptide is absent in EfBSH the mutation of these serines is tolerated. This suggests that an evolution-mediated subordination of the pre-peptide excision site resulted in loss of pre-peptide in EfBSH and other related Cholylglycine hydrolases.
Keywords: autocatalytic processing; Bile salt hydrolase; molecular dynamics; Mutagenesis; Polar complementarity; X-ray crystallography